Patterns of voluntary and replacement blood donors in a tertiary care center: a retrospective study - Sehgal, P. K.; Garg, Dinesh (International Journal of Research in Medical Sciences, 2017)
Background: Blood donor base is the foundation of any blood transfusion system. In India any able-bodied individual between the age of 18 and 60 years can donate blood. Blood donors are of two types: voluntary donors and replacement donors. Blood donation should be done by low risk population otherwise there is high risk of transfusion transmissible infections like HIV, hepatitis B, hepatitis C and malaria. The present study was conceived to see the patterns of blood donation among voluntary and replacement blood donors in tertiary care centre. Methods: In this study 50 (27 male and 23 female) adult skulls were investigated to determine the type of asterion, its distance from important bony landmarks and also the nearby venous sinuses were measured. Results: Of the total 340078, 298421(87.75%) collections were voluntary and 41657(12.25%) were replacement collections. A total of 2810 camps were held to gather blood through voluntary donors. Number of blood camps held show an increasing pattern as we progress in time. Also, the trends in voluntary blood donations increased over the period and more donors donated blood whereas replacement donors decreased over the period and eventually vanished in time. Conclusions: For a safe blood service in our country, where comprehensive laboratory tests are neither possible nor pragmatic, it is best to switch over to 100% voluntary donations, as it is now established that only voluntary non-remunerated regular donation is the safest. Thus, one of our key strategies to enhance blood safety is to focus on motivating non-remunerated blood donors and phasing out even replacement donors.